Morphological novelty and modest developmental truncation in Barboides, Africa's smallest vertebrates (Teleostei: Cyprinidae). (28th March 2017) - Conway, Kevin W.; Kubicek, Kole M.; Britz, Ralf
Abstract: Miniaturization, the evolution of extremely small adult body size, is widespread amongst animals and commonly associated with novel ecological, physiological, and morphological attributes. The phenotypes of miniaturized taxa are noteworthy because they combine reductions and structural simplifications with novel traits not developed in their larger relatives. Previous research on miniature cyprinid fishes (focused predominantly on South and South East Asian taxa of a single subfamily) has identified two distinct classes of miniature taxa: proportioned dwarves and developmentally truncated miniatures. Miniaturization has also occurred independently in the subfamily Cyprininae, particularly in African lineages. We investigate the skeletal anatomy of Barboides, a genus of miniature African cyprinids that includes Africa's smallest known species of vertebrates, to assess whether miniaturization has resulted in similar organismal outcomes in different lineages of the Cyprinidae. The skeleton of Barboides is characterized by the complete absence of a number of dermal and endochondral ossifications, and marked reduction in size and/or complexity of other skeletal elements, particularly those of the dermatocranium. Absent skeletal elements in Barboides include those which develop relatively late in the ossification sequence of the non‐miniature African relative ' Barbus ' holotaenia suggesting that their absence in Barboides can be explained by a simple scenario of developmental truncation. In contrast to this theme of loss and reduction, the os suspensorium of Barboides is enlarged and the outer arm distally trifid and associated with a novel bulbous muscle in males. An evaluation of the skeleton of Barboides provides further evidence for a link between developmental truncation and evolutionary morphological novelty in Cyprinidae. In the spectrum of miniature cyprinids ranging from proportioned dwarves with few bones missing to highly progenetic taxa with dozens of missing bones, the two species of Barboides range roughly in the middle showing that the extremes are connected by intermediate levels of truncatedness. Abstract : The skeleton of Barboides gracilis, one of the smallest African vertebrates, is characterized by the complete absence of a number of ossifications, and marked reduction of others. Large areas of cartilage (stained blue), typical of a larval skeleton, persist in the neurocranium, the gill arches, and the shoulder girdle.